2018
DOI: 10.1111/scs.12639
|View full text |Cite
|
Sign up to set email alerts
|

LGBTQ competence wanted: LGBTQ parents’ experiences of reproductive health care in Sweden

Abstract: Background It is the responsibility of reproductive healthcare professionals to support all lesbian, gay, bisexual, transgender, and queer (LGBTQ) parents in their transition to parenthood. LGBTQ parents may not be fully supported within the reproductive health sector, because of heteronormativity and healthcare professionals’ attitudes and practices. Beyond same‐sex mothers, no research has been conducted in Sweden on the broader group of LGTBQ parents. Aim To explore LGBTQ expectant and new parents’ experien… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
25
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(32 citation statements)
references
References 22 publications
1
25
0
Order By: Relevance
“…Fourteen studies noted that patients reported heteronormativity and cisnormativity as significant barriers to care (25)(26)(27)(28)(29)(30)(31)(32)(33)(34)(35). Examples of heteronormativity and cisnormativity included standardized forms that were designed for opposite-sex couples (28,30,33,34) and signage that excluded LGBTQþ parents (28).…”
Section: Barriers To Culturally Competent Carementioning
confidence: 99%
“…Fourteen studies noted that patients reported heteronormativity and cisnormativity as significant barriers to care (25)(26)(27)(28)(29)(30)(31)(32)(33)(34)(35). Examples of heteronormativity and cisnormativity included standardized forms that were designed for opposite-sex couples (28,30,33,34) and signage that excluded LGBTQþ parents (28).…”
Section: Barriers To Culturally Competent Carementioning
confidence: 99%
“…There are, for example, studies about heteronormative communication with lesbian families, 23 attitudes of health professionals towards LGBT persons in a range of healthcare settings 2426 and those held by nursing and medical students, 27,28 and attitudes of health professionals working in community early parenting services in two states of Australia. 29 Further, there is also research on LGBTQ families' experiences and needs in those settings. 17,18,26,30,31 Typically, those are dominated by studies on same-sex/lesbian motherhood, 31 and studies conducted on the broader group of LGBTQ parents in Nordic countries is still rare.…”
Section: Introductionmentioning
confidence: 99%
“…Surrogacy births among same-sex parents interrupt administrative guidelines, hospital policies, and medical discourses that employ heteronormative and gendered language. Thus, surrogacy practices may ultimately require a shift in language to be inclusive of same-sex parent families (Brennan et al, 2012;Klittmark et al, 2019;Stewart & O'Reilly, 2017). For example, post-birth orders, birth certificates, and health insurance documentation often employ heteronormative language; a lack of inclusive terminology that does not allow two men to assume parenthood creates additional hurdles that foster uncertainty, administrative errors, and frustration (Fantus, 2020(Fantus, , 2021aLev & Sennott, 2013;Shilo et al, 2016).…”
Section: Post-birthmentioning
confidence: 99%